New Insights in Trigeminal Anatomy: A Double Orofacial Tract for Nociceptive Input - Henssen, Dylan J. H. A.; Kurt, Erkan; Kozicz, Tamas; van Dongen, Robert; Bartels, Ronald H. M. A.; van Cappellen van Walsum, Anne-Marie (Frontiers in Neuroanatomy, 2016)
Orofacial pain in patients relies on the anatomical pathways conducting nociceptive information, originating from the periphery towards the trigeminal sensory nucleus complex (TSNC) and finally, to the grey matter structures located in the diencephalon and the somatosensorical cortical regions. The anatomy and function of the so-called trigeminothalamic tracts have been investigated before. In these animal-based studies the intracerebral pathways were mapped using different retro- and anterograde tracing methods. We review the literature on the trigeminothalamic tracts. The observations of these studies are related to clinical findings using fMRI trials. The trigeminothalamic tracts can be subdivided into three pathways: a ventral (contralateral) and dorsal (ipsilateral) trigeminothalamic tract and the intranuclear pathway. Based on the reviewed evidence we hypothesize the co-existence of a nociceptive ipsilateral conduction to the cerebral cortex and we translate evidence from animal-based research to the human anatomy. Our hypothesis differs from the current hypothesis that orofacial pain arises only from nociceptive information via the contralateral, ventral trigeminothalamic pathway. Better understanding of the histology, anatomy and connectivity of the trigeminal fibers could contribute to the discovery of a more effective pain treatment in patients suffering from various orofacial pain syndromes